1977
DOI: 10.1037/0022-006x.45.6.1060
|View full text |Cite
|
Sign up to set email alerts
|

Social insecurity and coronary-prone Type A responses as identifiers of severe atherosclerosis.

Abstract: Tests measuring the coronary-prone Type A behavior pattern, anxiety, and neuroticism were administered to 95 male patients undergoing coronary angiography. Item analyses suggest that men with more serious coronary atherosclerosis are hard-driving, hard-working Type A individuals who put pressure on themselves to solve problems, meet deadlines, and to move up the social ladder. At the same time, these patients are often uncomfortable in their interpersonal relationships and they feel awkward and insecure when i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
4

Year Published

1981
1981
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 14 publications
(20 reference statements)
0
16
4
Order By: Relevance
“…With regard to the social insecurity cluster, Type B's consistently scored higher than Type A's, which is in line with Glass's research on college students (2). These findings, however, are not consistent with previous work by Jenkins et al (30), which showed that the social insecurity items were independent of Pattern A. Differences in measurement instruments (the JAS versus the ASI and the BARS) and populations may be accounting for this disparity in findings.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…With regard to the social insecurity cluster, Type B's consistently scored higher than Type A's, which is in line with Glass's research on college students (2). These findings, however, are not consistent with previous work by Jenkins et al (30), which showed that the social insecurity items were independent of Pattern A. Differences in measurement instruments (the JAS versus the ASI and the BARS) and populations may be accounting for this disparity in findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Jenkins et al (30) have shown that social insecurity and heart disease are related in an adult population. However, social insecurity was found to be independent of Type A behaviors as assessed by the JAS.…”
Section: Dependent Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Questionnaires to measure these hypothetical personality types have been constructed (e.g. Jenkins, Zyzanski, Ryan, Flessas & Tannenbaum, 1977;Eysenck & Fulker, 1983, for CHD;Grossarth-Maticek & Eysenck, 1990, for cancer). There are two ways of providing construct validity, namely (1) demonstrating that probands high on Type C are diagnosed as suffering from cancer, while probands high on Type A are diagnosed as suffering from coronary heart disease, more frequently than vice versa, and that probands of Type B are found to be healthy.…”
Section: Introductionmentioning
confidence: 99%
“…C. D. Jenkins et al (1977) stated that type A individuals do not feel negative emotional affectivity in stressful situations, because they tend suppress the recognition of physiological discomfort associated with the behavioural pattern. However, some studies revealed that Type A behaviour pattern is related with emotional distress and neurotism (Cramer, 1991;Moriana, Heruzo, 2005).…”
Section: Introductionmentioning
confidence: 99%